Medical publication and role of Artificial Intelligence - Bhandari, Jeetendra (Journal of Karnali Academy of Health Sciences, 2025)
Artificial Intelligence (AI) is transforming the way medical knowledge is created and shared, making it crucial for journals to utilize it responsibly, with transparency, oversight, and safeguards to ensure fairness and accountability. AI is already assisting with tasks such as plagiarism checks, data verification, and workflow management, which accelerates decision-making but also introduces integrity risks if not adequately supervised. Current guidelines emphasize that AI cannot be listed as an author, and any AI assistance should be clearly disclosed and attributed to the human author. In editorial processes, AI can assist with organizing literature, verifying figures and tables, enhancing language clarity, identifying duplicates, analyzing images, and detecting anomalies, thereby freeing up reviewers to focus on the clinical significance. Ethical policies should require clear disclosure of AI tools and their roles, protect data confidentiality, and maintain human responsibility for accuracy and originality. Due to risks such as AI-generated hallucinations and fake citations, journals should restrict submissions generated by AI, require detailed disclosures from authors, and combine automated checks with human review and audit trails.